Managing atopic dermatitis with systemic therapies in adults and adolescents: An Australian/New Zealand narrative. (16th September 2019) - Rademaker, Marius; Agnew, Karen; Andrews, Megan; Baker, Christopher; Foley, Peter; Gebauer, Kurt; Gupta, Monisha; Rubel, Diana M.; Somerville, Colin; Sullivan, John; Wong, Li‐Chuen
Abstract: With the rapid development of new, targeted therapies for the treatment of moderate/severe atopic dermatitis, it is opportune to review the available conventional systemic agents. We assess the published evidence for systemic therapies for atopic dermatitis and amalgamate this with real‐world experience. Discussions are centred on when systemic therapy should be considered, which drug(s), what dose, how to sequence or combine these therapies, how long they should be continued for and what is considered success.